Phase-selective recrystallization makes eutectic high-entropy alloys ultra-ductile - Wu, Qingfeng; He, Feng; Li, Junjie; Kim, Hyoung Seop; Wang, Zhijun; Wang, Jincheng (Nature communications, 2022)
Excellent ductility is crucial not only for shaping but also for strengthening metals and alloys. The ever most widely used eutectic alloys are suffering from the limited ductility and losing competitiveness among advanced structural materials. Here we report a distinctive concept of phase-selective recrystallization to overcome this challenge for eutectic alloys by triggering the strain hardening capacity of the duplex phases completely. We manipulate the strain partitioning behavior of the two phases in a eutectic high-entropy alloy (EHEA) to obtain the phase-selectively recrystallized microstructure with a fully recrystallized soft phase embedded in the skeleton of a hard phase. The resulting microstructure fully releases the strain hardening capacity in EHEA by eliminating the weak boundaries. Our phase-selectively recrystallized EHEA achieves a high ductility of ∼35% uniform elongation with true stress of ∼2 GPa. This concept is universal for various duplex alloys with soft and hard phases and opens new frontiers for traditional eutectic alloys as high-strength metallic materials. The ever most widely used eutectic alloys often suffer from limited ductility. Here the authors propose a distinctive concept of phase-selective recrystallization to significantly improve their ductility and strength and pave the way for new applications of the widespread eutectic alloys.